Study to Improve the Spindle Bearing Stiffness of Medium External Cylindrical Grinding Machines Based on Numerical Simulation of Hydrostatic Lubrication - Pham, Van-Hung; Bui, Tuan-Anh; Nguyen, Thuy-Duong (Old Journal, 2018)
Medium-sized cylindrical grinding machines are fine-machining machine tools, which are widely used in the manufacturing industry. Accuracy of grinding process depends mainly on the precision and working quality of the spindle unit, in which the stiffness of the spindle bearings plays an important role. On the spindle bearings of external cylindrical grinding machine, the machine is usually uses hydrodynamic bearing with three self-aligning pad, which allows the machining workpiece to achieve a rounded and accurate diameter up to 0.005 mm. Based on the hydrostatic lubrication theory as well as the current fabrication and fabrication capabilities of the self-aligning pad of hydrodynamic bearing spindle, this paper presents the results of calculation and numerical simulation to improve the bearing film stiffness of the medium cylindrical grinding machines with a reasonable hydrostatic parameters.